COMPERATIF STUDY OF ATOMS FISH CRACKER PROCESSING JELAWAT (Leptobarbus hoevenii Blkr) WITH THE USE OF FISH MEAT AND FISH MEAL FOR CONSUMER ACCEPTANCE - Jufrizal Yasin; Desmelati '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study was purposed to determine the consumer acceptance of common carp (Lepotobarbus hoevenii Blkr) atom crackers that added with fish meat compared to that added with fish meal. The fish meal was obtained from traditional markets. The fish initially was processed into fish meal and mixed with tapioca flour, water, seasoning and condiments and then fried. The quality of fish crackers produced was assessed for their consumer acceptance and their chemical composition. The fish cracker added with the fish meat showed the highest consumer acceptance at the rate of 100%. The fish cracker added with the fish meat contained 6,10% moisture, 29,46% protein, 7,00% fat and 2,17% ash.Keywords: atom crackers, consumers acceptance, fish meal, Leptobarbus hoevenii Blkr